Changes in cannabis use post decriminalisation in mental health care users in South Africa - Rachel Moshori; Lisa Galvin; Laila Paruk (South African Journal of Psychiatry)
Background: Personal cannabis use was decriminalised in South Africa in 2018. Cannabis use increases the risk of mental illness (MI) and worsens prognosis in patients with MI. The impact of decriminalisation on cannabis use remains unclear.